Activation of defense mechanisms in pyre corn through the use of Microgeo® organic fertilizer - Posso Suárez, David Fernando; Mattos, Amanda do Prado; Broti Rissato, Bruna; Schwan-Estrada, Kátia Regina Freitas (Revista Mexicana de Ciencias Agrícolas, 2020)
The induction of resistance (IR) in plants by natural products has been the subject of several studies, these being activated by eliciting molecules of biotic or abiotic origin. Elicitors activate resistance mechanisms such as pathogenesis-related proteins (PRP’s), which act to protect plants by preventing pathogen development. The present study aims to verify the activation of PRP's (peroxidase, catalase, polyphenoloxidase and β-glucanase) in pyre corn plants (Zea mays) treated with different concentrations (0%, 0.5%, 1%, 1.5%, 3% and 5%) of the commercial biofertilizer Microgeo®. Analyzing the PRP’s enzymes, it was observed that the Microgeo® activated and increased the activity of these enzymes and that this induction is more related to the activation time, but not to the concentration used.
Keywords: defense mechanism; enzymatic activity; induced resistance; inducers